Interaction Between Hydrodynamics and Chemical Reaction Rate in a Vertical Gas-Slurry Cocurrent Turbulent Tube Reactor. I. Performance Indicators - Cantero, Héctor (2000)
To analyze the performance of a vertical tube reactor involving a gas-slurry reacting system in dispersed bubble flow and upflow, downflow, and upflow-downflow (alternating) configurations, several performance indicators are defined and expressed in terms of integral equations. A local effectiveness factor associated with the efficiency for gas-slurry mass transfer, conversion of the liquid reactant, the local unconverted mass fraction of the gas phase, and the pressure drop are taken as performance indicators. Bounding criteria for diffusion-controlled and chemical reaction-controlled regimes are established, and their transitions along the reactor are also discussed. A generic heterogeneous catalytic hydrogenation, exemplified by the single reaction A(l) + H2(g) -> B(l), is taken as a suitable reference system.